(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This study addresses the production of moving images and the importance of cinema-education practices in basic education, from the perspective of different literacies and an education focused on sensitivity. Thus, the article seeks to problematize and propose reflections on how these approaches can impact teaching in basic education. The central question investigated is: “How can the production of moving images be used as a means of stimulating sensitivity and promoting students’ autonomy?” Based on this question, the need to reformulate pedagogical practices in light of the challenges imposed by digital culture is problematized, seeking to establish relationships between the production and use of images in the classroom, based on the methodology adopted by Escola Semente Educação Audiovisual, aimed at classes in the early years of Elementary School.